High-stable mesoporous Ni-Ce/Clay catalysts for syngas production (2011)
ABSTRACT: A mesoporous-type catalytic support was synthesized through the modification of a smectite with polyvinyl alcohol (PVA) and microwaves. Texture and micro- morphology of the support was determined. Several techniques were employed in order to describe the chemical environment of active species on the surface. Ni0 particle sizes were dependent on the structural site of reducible species. High stable Ni-Ce catalysts (calcined at 800 °C) were evaluated in the CO2 reforming of methane reaction at 700 °C (WHSV = 96 L g−1 h−1, without dilution gas and pre-reduction). The catalysts have presented CH4 conversions between 40 and 65%, CO2 conversion between 35 and 65% and H2/CO ratios between 0.2 and 0.4.